Khaki and the ethnic violence in India Army,Police And Paramilitary Forces during Communal riots - Khalidi, Omar (New Delhi, 2003)
India s military, paramilitary, and the police constitute one of the largest security forces around the globe. Who constitutes these forces? What is the ethnic and religious background of these troops? Does the composition of these forces mirror the diversity of the Indian society? Have their composition undergone any change since Independence? Like other nations with ethno-religious diversity, India has experienced half a century of ethnic riots, massacres, even pogroms. What impact, if any does the ethnic and religious composition of the security personnel has on the ability of the state to prevent the occurrence of ethnic violence or to mitigate loss of lives and property once it occurs? Answers to these questions are critical to anyone interested in understanding the role of the state s most critical instrument of legitimate coercion the security forces. This book provides the answers with precision and economy of words. In this respect Khaki and the Ethnic Violence in India simply has no rival.
Keywords: Violence